Trust of social media content and risk of making misinformed decisions: Survey of people affected by cancer and their caregivers - Ilona Fridman; Carma L. Bylund; Jennifer Elston Lafata (PEC Innovation)
Background: This study explores social media (SM) usage and trust in information among cancer patients and their caregivers. We compare socio-demographic characteristics to identify groups more likely to rely on social media for treatment decisions and those less inclined to validate social media information with their provider. Methods: A national survey of people diagnosed with cancer and those who were caregivers to people diagnosed with cancer was conducted via online survey in November–December 2021. Socio-demographic factors associated with respondents' use of SM and comfort disclosing SM use were assessed using logistic regression. Findings: Out of 262 respondents, 65% were likely to use SM to make decisions about lifestyle changes, cancer screening, vaccination, cancer treatment, medical testing, or choosing a provider. SM users were younger (ORadj = 0.11, p < 0.01), identified as Black (ORadj = 10.19, p < 0.01), and had less education (ORadj = 0.86, p = 0.02). Those with less education reported not being comfortable discussing SM with their providers (ORadj = 1.25, padj = 0.01). Discussion: Results contribute new understanding of the digital divide, highlighting the need for not only improving access to digital information but also the need for a supportive environment that provides patients with dependable methods to verify the authenticity of the information they encounter.